Effect of Fragmented DNA From Plant Pathogens on the Protection Against Wilt and Root Rot of Capsicum annuum L. Plants - Serrano-Jamaica, Luz Maria; Villordo-Pineda, Emiliano; González-Chavira, Mario Martín; Guevara-González, Ramón Gerardo; Medina-Ramos, Gabriela (Frontiers in Plant Science, 2021)
Chili pepper (Capsicum annuum L.) production is affected by wilt and root rot, the most devastating disease caused by the pathogen complex of oomycete Phytophthora capsici Leon and the fungi Fusarium oxysporum Schlecht and Rhizoctonia solani Kühn, infecting roots, stems, leaves, and fruits. Fungicides are currently inefficient against this disease and have a high environmental impact. The use of elicitors is a sustainable alternative for inducing resistance to wilting and root rot. DNA fragments of an organism’s own origin (conspecific or self-DNA) have shown the ability to inhibit growth and activate defense mechanisms in some plant species. In this investigation, the effect of the fragmented DNA mixture of Phytophthora capsici L., Fusarium oxysporum S., and Rhizoctonia solani K. on the protection against wilt and root rot of Capsicum annuum L. plants was evaluated. Changes in plant performance, phenolics, and flavonoids contents, as well as gene expression involved in the production of defense metabolites after the fragmented and unfragmented DNA mixture in three concentrations (20, 60, and 100 μg mL–1) in chili peppers, were studied. The results obtained showed a decrease in plant height in 60 and 100 μg mL–1 concentrations in absence of pathogens. Moreover, the treatment with fragmented DNA 100 μg mL–1 showed significant increase in the content of phenolic compounds and total flavonoids as well as gene expression associated to plant defense in comparison with control plants. Interestingly, foliar application of DNA fragments of the pathogen complex to a concentration of 100 μg mL–1 caused a 40% decrease in the mortality of infected plants with the pathogens at 30 days post-inoculation compared with control plants inoculated with the pathogen complex but not sprayed with DNA fragments. These results suggested a perspective for application of fragmented DNA of these pathogens at the agricultural level in crop protection strategies to cope with wilt and root rot in Capsicum.